Dobroczynność w Rosji w świetle publikacji w czasopismach i almanachach literackich pierwszej połowy XIX wieku - Dąbrowska, Magdalena (Studia Rossica Posnaniensia, 2020)
The article presents the publications in the periodical “Zhurnal Imperatorskogo chelovekolubivogo obshchestva” and the literary almanac Podarok bednym in the light of the development of charity in Russia (motives, forms, results): 1. The publications of Alexander Sturdza (About social charity, About private charity), Pyotr Shalikov etc.; 2. The charity institutions in the capital and the provinces; 3. The charity initiatives of women and the Russian writers. “Zhurnal Imperatorskogo chelovekolubivogo obshchestva” (the monthly magazine) was published in St. Petersburg from 1817 to 1826. It contained, among other elements, information and reports about the activity of philanthropists and charity institutions, and literary works (Hymn to love for a man by Pyotr Shalikov). Podarok bednym was published in Odessa in 1834 (the motto was a quotation from the Aeneid by Vergil: “Miseris succurrere disco”) by a women’s benevolent society. It contained the commentaries and works of belles-lettres. The paper compares “Zhurnal Imperatorskogo chelovekolubivogo obshchestva” and Podarok bednym (the “common places”, for instance the articles by Alexander Strudza About social charity published in “Zhurnal Imperatorskogo chelovekolubivogo obshchestva” in 1817 and in Podarok bednym in 1834). It presents also the discussions about charity in the Russian periodicals in the first half of the 19th century.